Static Coldcure Vulcanization On Embossed Rubber Cotsheets Using Chambers - Fam, Tony Chee Hoe (2019)
Vulcanization is a technological process in rubber production in which raw rubber is converted into cure rubber. In the static coldcure process, vapor or fumed sulphur monochloride (S2C12) is used to cure the embossed rubber cotsheet in a chamber. Since the embossed cotsheet is not agitated during the vulcanization process, therefore the end products have no folded marks on its surface after being cured. However, the top and bottom surface may be not uniformly cured if the vapor sulphur monochloride is not well contralled. Too high of temperature also can cause the bubbles over expand and become deformed after cooling down. These two factors result in collapsed bubbles on the cotsheet products. Condensation of the sulphur monochloride inside the chamber also leads to formation of sulphur stains which can contaminate the cotsheet. These two main defects result in high product rejection and heavy customers’ complaints. Therefore various process parameters such as vulcanization time. inner temperature of chamber, pot surface temperature and amount of sulphur monochloride that cause these two issues need to be studied. Design of Experiment (DOE) was carried out using Response Surface Methodology (RSM). Data collected were analyzed in the Design-Expert 6.0.8 Portable software. The results show that internal heating piping temperature which contributes to the inner temperature of chamber has significant p value (<0.05) to the response of collapsed bubbles and sulfur stains. The amount of (S2Cl2) is significant to the collapsed bubbles only. Whereas, the other variables, pot surface temperature and vulcanization time are insignificant o the both responses. Optimization analysis shows that the optimum parameters to minimize both responses are internal heating pipe temperature 0.6kg/cm2, pot surface temperature 4.0 kg/cm2, vulcanization time 15 minutes and S2Cl2, amount 450ml.